Moral Attitudes & Mental Disorders - Scheurich, Neil (The Hastings Center report, 2002)
When psychiatrists treat patients with mental disorders—when clinicians of any stripe have a “difficult patient”—they confront and must come to terms with the thought that the patient is morally responsible for his conduct. Taken to its extreme form, this attitude leads to a repudiation of the whole concept of mental illness. In a modest form, and held perpetually in tension with an objective, clinical stance toward mental disorders, it is an ineluctable part of the practice of psychiatry.